Rancang Bangun Sistem Monitoring Getaran pada Jalan Tol - Erna Kusuma Wati; Ayu Maharani Larasati Putri (Radial : Jurnal Ilmiah Sains dan Rekayasa, 2023)
The construction of toll roads is one of the infrastructure developments; however, the construction of new toll roads is often hindered by complaints from residents in the surrounding areas who feel disturbed by the vibrations caused by vehicles on the toll road. Therefore, there is a need for a vibration monitoring tool that can monitor vibration acceleration. This research has successfully developed an online vibration monitoring tool on the toll road using the MMA7361 accelerometer sensor. Field measurements were conducted for approximately 30 minutes on the edge of the Jakarta-Serpong toll road, specifically at Km-11. Data transmission was done online using the ESP8266 WiFi module and utilizing a portable WiFi hotspot from a cellular phone. The results showed that the magnitude of gravity acceleration changes due to passing vehicles. The measured gravity acceleration value within a distance of 1 meter from the slow lane or approximately the edge of the road shoulder never exceeded 0.5 m/s². At a distance of 10 meters away from the edge of the road shoulder, the gravity acceleration value became 0.07 m/s², which is the threshold that is not perceivable by humans and does not damage any structures.